Pengaruh Teknik Kampanye Digital Public Relations #WeGotYou Terhadap Corporate Branding Gojek: Survei Terhadap Followers Instagram @gojekindonesia - Kania Untari Salsabila; Nani Nurani Muksin (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Gojek is an online transportation application company in Indonesia that has created a strategy to increase corporate branding, one of which is by conducting campaigns.the campaigns created by Gojek are always related to the current conditions of society so that people can easily feel the effects of the campaign. In relation to this, this research aims to measure the influence of Gojek #WeGotYou public relations campaign on Gojek corporate branding, Gojek #WeGotYou public relations campaign, corporate branding obtained by Gojek. This research uses theory, namely a public relations campaign which includes participacing, association, integrative, pay of technique, icing technique, empathy, coercion technique. The approach used in this research uses a quantitative approach, which uses survey methods. This research is included in the descriptive research category quantitative. The data collection technique was carried out by distributing 148 respondents to people who commented on the #WeGotYou campaign upload on Instagram @gojekindonesia, the sampling method used random sampling. The results of this research show that the influence of the #WeGotYou public relations campaign on respondents responded well (agree) to all the statements submitted and on corporate branding the respondents responded well (agree), which means, there is an influence between the #WeGotYou public relations campaign on Gojek's corporate branding. Based on the hypothesis test that has been carried out, this research has a number of respondents (n) = 148, so the degrees of freedom (df) n – k = 148 – 2 = 146. With degrees of freedom of 146 and a significance of 5%, it is 1.97635 rounded to 1.976. Because the value of count (18.758) > ttable (1.976), H0 is rejected. H1 is excepted, which means there is an influence between the #WeGotYou Public Relations Campaign on Gojek's Corporate Branding. This research has an R square value of 0.707. The R square value shows a figure of 0.707 or 70.7%, which means that there is an influence between the #WeGotYou Public Relations Campaign on Gojek Corporate Branding.